2015
DOI: 10.1016/j.actpsy.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Dot comparison stimuli are not all alike: The effect of different visual controls on ANS measurement

Abstract: Additional Information:• This paper was accepted for publication in the journal Acta twice to obtain a measure of immediate test-retest reliability. We found no significant correlation between participants' accuracy scores on trials created with the two protocols, suggesting that tasks employing these protocols may measure different cognitive constructs.Additionally, there were significant differences in the test-retest reliabilities for trials created with each protocol. Finally, strong congruency effects fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
164
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(187 citation statements)
references
References 40 publications
20
164
3
Order By: Relevance
“…The default radius of the dots was 60 pixels and the maximum variability in size between the dots was +/−35%. Previous research has found that non-numerical aspects of an array can affect numerical performance (Clayton, Gilmore, & Inglis, 2015; Gebuis & Reynvoet, 2012; Smets, Sasanguie, Szücs, & Reynvoet, 2015). As such, on half of the trials the two arrays were equated for individual dot size (i.e., the average size of the dots in each collection was equal).…”
Section: Methodsmentioning
confidence: 99%
“…The default radius of the dots was 60 pixels and the maximum variability in size between the dots was +/−35%. Previous research has found that non-numerical aspects of an array can affect numerical performance (Clayton, Gilmore, & Inglis, 2015; Gebuis & Reynvoet, 2012; Smets, Sasanguie, Szücs, & Reynvoet, 2015). As such, on half of the trials the two arrays were equated for individual dot size (i.e., the average size of the dots in each collection was equal).…”
Section: Methodsmentioning
confidence: 99%
“…accuracy or RT; Inglis & Gilmore, 2014). In particular, the visual characteristics of dot arrays have been shown to have substantial impact on participants’ performance (Clayton, Gilmore, & Inglis, 2015; DeWind & Brannon, 2016; Gebuis & Reynvoet, 2012; Smets, Sasanguie, Szücs, & Reynvoet, 2015). Studies have shown that performance on dot comparison tasks is dependent on how the visual characteristics of arrays are controlled and, in particular, how many visual cues are controlled (Gebuis & Reynvoet, 2012; Smets et al., 2015).…”
mentioning
confidence: 99%
“…Researchers use a variety of methods to control for visual characteristics in the construction of dot arrays (e.g. Gebuis & Reynvoet, 2011; Halberda et al., 2008; Pica, Lemer, Izard, & Dehaene, 2004; see Clayton et al., 2015 for examples of stimuli from different methods). Typically this involves the creation of congruent trials, in which one or more visual cues are positively correlated with numerosity, and incongruent trials, in which one or more visual cues are negatively correlated with numerosity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2Note however, that there is an ongoing debate about choice of methods to control for visual cues, and that more elaborate methods that control over several dimensions including convex hull result in measures that are apparently not related to measures obtained with more basic controls (see Clayton et al, 2015; Smets et al, 2015). …”
mentioning
confidence: 99%